THE PROMINENCE OF THE PEAKS FROM RODNEI MOUNTAINS (ROMANIA) WITH RELEVANCE FOR MOUNTAINEERING. METHODOLOGICAL AND PRACTICAL ASPECTS - Ioan BÎCA (Cluj University Press, 2019)
In recent years, mountain leisure activities in Romania recorded spectacular growth, due to several factors, such as: technical progress in the field of mountain equipment, increased leisure and circulation of information on the internet or in the media. If in the past, mountain tourism activities belonging, to a certain extent, of niche tourism, today they fall into mass tourism and one of the criteria that attract the mountaineers to mountain areas is altitude and prominence of the peaks. The higher the altitude, the more attractive and competitive the respectively peak. The prominence is a parameter that refers to the gap between top and base of the peak, marked by neighboring saddles called key-saddles or key-col. According UIAA, minimal prominence for a mountain/hill structure to be considered peak with relevance for sports activities is 30 m (a rope length). Between altitude and prominence of the peak is not necessarily a relation, therefore, often, more important is the last one, who actually, identifying the peak. Therefore, in this study it approached Rodnei Mountains area, which was manually calculated the prominence of the peaks from main ridge, in order to underline the importance of this sector for various leisure activities. REZUMAT. Proeminența vârfurilor din Munții Rodnei, cu relevanță pentru muntenărie. Aspecte metodologice și practice. În ultimii ani, agrementul montan din România a înregistrat creșteri spectaculoase datorită mai multor factori, cum ar fi: progresul tehnic din domeniul echipamentului montan, creșterea veniturilor, creșterea timpului liber și circulația informației pe internet sau în mass media. Dacă în trecut, activitățile turistice montane aparțineau, într-o anumită măsură, turismului de nișă, astăzi acestea se încadrează în turismul de masă, iar unul dintre criteriile care atrag muntenarii spre arealele montane este altitudinea și proeminența vârfurilor. Cu cât este mai mare altitudinea, cu atât este mai atractiv și mai competitiv vârful respectiv. Proeminența este un parametru care se referă la diferența de nivel dintre creștetul vârfului și baza sa, marcată de înșeuările limitrofe, numite înșeuări-cheie. Conform UIAA, proeminența minimă, pentru ca o structură montană să fie considerată vârf cu relevanță pentru activități sportive este 30 m (o lungime de coardă). Între altitudinea și proeminența vârfului nu este, neapărat, o legătură, de aceea, de multe ori, este mai importantă aceasta din urmă, care individualizează, de fapt, vârful. Prin urmare, în studiul de față s-a abordat arealul Munților Rodnei, pentru care s-a calculat manual proeminența vârfurilor de pe culmea principală, cu scopul de a sublinia importanța acestui sector pentru diferitele activități agrementale. Cuvinte cheie: turism montan, agrement montan, înșeuare-cheie, nivel de bază, vârf independent, vârf părinte, dominanță orometrică